Translation, Cultural Adaptation, and Validation of the Indonesian Version of the Quality of Oncology Nursing Care Scale (QONCS) - Novrianda, Dwi; Malini, Hema; Sarfika, Rika; Rusana, Rusana; Hayati, Mala; Truong, Pham Van (Fakultas Ilmu-ilmu Kesehatan, 2024)
A validated instrument is crucial for assessing oncology nursing care in Indonesia. This study focused on translating, adapting, and validating the QONCS among Indonesian cancer patients and families. Initial feedback from nursing academicians and pilot participants guided the adaptation process. Validation involved distributing the instrument via Google Forms to 8 cancer referral hospitals, gathering responses from 148 individuals. Confirmatory factor analysis (CFA) assessed validity, while Cronbach's alpha measured internal consistency. Synonyms and examples were added to enhance item clarity. Eight items were removed due to poor construct validity, resulting in improved statistics (r statistic: 0.653-0.818; average variance extracted: 0.742). The revised instrument demonstrated high reliability (Cronbach's alpha: 0.967). This study confirms the Indonesian QONCS version as a valid and reliable tool for evaluating oncology nursing care. It is recommended for oncology nurses to utilize the QONCS to enhance the quality of care provided.